Clonorchis sinensis and Echinostoma hortense detected by endoscopy and molecular characterization: two case reports and update on diagnosis - Wen, Lijia; Wang, Benhe; Zhang, Hui (Frontiers in Medicine, 2025)
Clonorchis sinensis (C. sinensis) and Echinostoma hortense (E. Hortense) infections represent significant food-borne zoonotic parasitic diseases. C. sinensis stands as the primary parasite underlying cholangitis, cholelithiasis, and even cholangiocarcinoma, whereas E. Hortense parasitizes the duodenum. Unfortunately, the non-specific clinical presentations of these two trematodes frequently mislead clinicians, resulting in overlooks or misdiagnoses, and consequently, inadequate treatment. We diagnosed digestive system trematodes through endoscopic observation and molecular methods. Herein, we present a case where C. sinensis was definitively diagnosed through direct observation under duodenoscopy. For the first time, we captured the entire migratory process of the parasite from the common bile duct into the intestinal lumen. In another case, multiple active trematodes were detected on the duodenal wall under duodenoscopy, subsequently extracted using endoscopic forceps. Based on the morphology of the worms and their eggs, an initial diagnosis of Echinostoma was made. To confirm the species, we designed primers targeting the ribosomal ITS (internal transcribed spacer) and mitochondrial COX-1 (cyclooxygenase-1) genes, followed by PCR amplification and sequencing. The results conclusively matched the sequence of E. Hortense, verifying our final diagnosis. Our proposed approach, integrating endoscopy with molecular characteristics, offers novel strategies for diagnosing trematode infections. This methodology represents a significant advancement in the field, enhancing the accuracy and timeliness of treatment interventions.